A Cystic Clival Chordoma with CT and MRI Unconventional Appearances - Guadalupi, Pamela; Gessi, Marco; Massimi, Luca; Caldarelli, Massimo; Gaudino, Simona (Indian Journal of Radiology and Imaging, 2022)
We present the first case of clival cystic chordoma with extradural location, transdural transgression, and moderate bone involvement in a 10-year-old girl. Chordoma showed unconventional appearances on computed tomography (CT) and magnetic resonance imaging (MRI), due to cystic components, extradural space location with extensive intradural extension, moderate superficial bone involvement. Surgery confirmed the extradural location and histopathological examination revealed cystic chordoma. MRI and CT findings were not characteristic for a single lesion; differential diagnoses included cystic lesions such as epidermoid and dermoid cyst, ecchordosis physaliphora, and benign notochordal cell tumors.
Keywords: chordoma; CT; cystic; extradural; MRI; transdural